A Sesquiterpene Aldehyde Isolated From Ethyl Acetate Extract of Lansium Domesticum Fruit Peel - Khusnul Fadhilah; Subagus Wahyuono; Puji Astuti (Universitas Gadjah Mada, 2021)
Lansium domesticum (fam. Meliaceae) contains various compounds with various biological activities. Based on the previous research, extracts from several parts of the plant have biological activity. This study aimed to isolate a compound from the fruitpeel of L. domesticum and evaluate cytotoxic activity against T47D, WiDr and HepG2 cell lines. Powdered peels were macerated with ethyl acetate and the filtrate was evaporated to give EtOAc extract. Dried extract was triturated with n-hexane to give n-hexane soluble fraction (A) and insoluble fraction (B). The fraction B was separated using vacuum column chromatography (VLC) with mobile phase n-hexane: ethyl acetate and given 5 fractions. Fractions B3-B5 were combined and separated using VLC with n-hexane and ethyl acetate as mobile phase. This VLC separation gave 18 subractions, subfractions 6-9 with the similar TLC profile were combined. This subfraction was separated further using preparative thin layer chromatography to give compound 1. The Isolated compound (1) appeared as liquid. The chemical structure of 1 was identified acoording to spectroscopic data and comparison with literature. Cytotoxic bioassay was performed on T-47D, WiDr and Hep G2 cell lines in a series of concentrations at 50, 40, 30, 20, 10 and 5µg/mL, with Doxorubicine used as positive control. According to spectroscopic data, compound 1 was identified as 2-ethyl,3-(1'-hydroxy-2'-menthene) propenal, and demonstrate the strongest cytotoxicity against T-47D cell lines (IC50=39.18+1.54 µg/mL).